Pembuatan Mesin Pengiris Tempe - Algusra, Jeri; Mukhnizar, Mukhnizar; Zulkarnain, Zulkarnain; Abu , Risal; Afdal, Afdal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Slicing tempeh, which is generally done manually, can slow down the production process. Therefore, a tool was designed that is capable of slicing tempeh precisely, so that the results of slicing tempeh are more precise, efficient, save time, save labor, and reduce the possibility of work accidents. . In making this tempeh slicing machine, a ½ HP 1400 Rpm electric motor is the main driver, the rotation of the electric motor is transmitted to the cutting knife (circular knife), which will later be used to slice the tempeh. The tempeh slicing process is done by placing the tempeh on a sliding table slide. The basic materials used in making a tempeh slicing machine are 4x4 hollow iron, a dynamo adapter, and an electric motor. After the tool was ready to be used, the tempeh slicing machine was tested. The test was carried out for 10 seconds and produced 8 tempeh slices, 5 suitable tempeh slices and 3 unfit tempeh slices, so it could be concluded that the suitability of the tempeh slicing results was 68 percent